Experience Bali in Japan: A Short Trip to Nasu Highland - Akinori Wada (Bali Tourism Journal, 2020)
COVID-19 outbreak around the world made overseas travel almost impossible. Thus, for this summer holiday, Nasu may be opted as destination to spend freetime with family. Located in the northeast of Tochigi prefecture, Nasu is a rural town set in a vast mountain range. The area is famous for its attractions such as onsen, themed park and winter sports. There is also a historical sightseeing Sessho-seki, Nasu Yumoto Onsen, and Imperial villa. Those who wish to experience overseas experience may visit the mini theme park of the Asian old bazaar, located on Nasu Road in Tsumujiga-daira Yumoto, Nasu Town. There we can find shopping complexes with Asian themes such as Vietnam, India, Nepal, Thailand and Bali. Ubudo Restaurant, a restaurant decorated with Balinese architecture, offers a variety of Balinese culinary specialties. The Balinese vibe is strongly-felt right after entering the restaurant's Candi Bentar gate, which perfected the dining experience in Bali. The visitor may also visit many favorite spots such as Nasu ropeway, Minamigaoka Bokujo, the Monkey Park, the Museum of Cars, the Teddy Bear Museum, and the Animal Kingdom tourist park that should not be missed.